Effectiveness of Apple Cider Vinegar Immersion with and Without Mother as a Decrease in Lead (Pb) Levels in Green Mussels (Perna viridis) - Muhibbatul Jannah, Siti Nur; Farpina, Eka; Aina, Ganea Qorry (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Lead is a heavy metal that often pollutes aquatic biota such as green mussels. Green mussels that contain lead if consumed in humans can pose health risks such as long-term assumptions or in high levels can cause poisoning. To reduce the lead level, we can use apple cider vinegar with and without mother which contains acetic acid and citric acid. The purpose of this study is to observe lead levels of green mussels after soaking with apple cider vinegar with and without mother, percentage decrease in green mussels lead content and the effectiveness of apple cider vinegar with and without mother in reducing lead levels. This study was a quasi-experiment by soaking green mussels using apple cider vinegar with and without mother for 5, 10, 15 minutes. The sample is prepared by drying the sample in the oven and extracting the sample using wet destruction so that a clear liquid is obtained that can be measured using an atomic absorption spectrophotometer. The results showed that the average lead levels sample soaked by apple cider vinegar with mothers were 0.219 mg/L, 0.103 mg/L, 0.088 mg/L, without mothers were 0.205 mg/L, 0.173 mg/L, 0.125 mg/L. The percentage of lead decrease was 2.6%, 49%, 51% used apple cider vinegar with mother while without mother is 8%, 15%, 30%. After the one-way ANOVA test, a p-value of > 0.05 was obtained with no effect of lead reduction. Based on research apple cider vinegar with and without mother can reduce lead levels, but statistically, the decrease is not significant.